Theoretical Foundations of the Development of Social Infrastructure (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is dedicated to the theoretical foundations of social infrastructure services that affect the quality and improvement of the standard of living of the population. The article describes the composition of the elements of social infrastructure and their classification.